Bibliophile values of the “Universitary Deposit” collection of the “Nicolae Testemiţanu” Chisinau State University of Medicine and Pharmacy (Confluenţe Bibliologice, 2018)
The authors present the collections of publications „The University Depository” of “Nicolae Testemiţanu”,Chisinau State University of Medicine and Pharmacy , which is part of the fund of the Department of Preservation and Communication Collections. This section is meant to store, preserve and keep a copy of the publications of the academic staff of USMF “Nicolae Testemitanu”, the publications about their activity, as well as publications related to the history, activity of the University. DU collection fund includes approximately 6100 copies, studies, dictionaries, university courses, textbooks, guides, etc. The aim of the research was to highlight the most significant publications in the DU collection, which are authentic bibliophile values for the university medical patrimony.
Keywords: bibliophile values; library collections; institutional repositories